Encephalitis with prolonged but reversible splenial lesion - Meleková, Alena; Andrlová, Leona; Král, Pavel; Ungermann, Leoš; Ehler, Edvard (Acta Medica, 2015)
INTRODUCTION: The splenium of the corpus callosum has a specific structure of blood supply with a tendency towards blood-brain barrier breakdown, intramyelinic edema, and damage due to hypoxia or toxins. Signs and symptoms of reversible syndrome of the splenium of the corpus callosum typically include disorientation, confusion, impaired consciousness, and epileptic seizures. CASE REPORT: A previously healthy 32-year-old man suffered from weakness, headache, and fever. Subsequently, he developed apathy, ataxia, and inability to walk, and therefore was admitted to the hospital. Cerebrospinal fluid showed protein elevation (0.9 g/l) and pleocytosis (232/1 ul). A brain MRI showed hyperintense lesions in the middle of the corpus callosum. The patient was treated with antibiotics, and subsequently, in combination with steroids. Two months later, the hyperintense lesions in the splenium and the basal ganglia had disappeared. Almost seven months since his hospitalization in the Department of Neurology, the patient has returned to his previous employment. He now does not exhibit any mental changes, an optic edema and urological problems have improved. In addition, he is now actively engaged in sports. CONCLUSION: We have described a case of a 32-year-old man with confusion, ataxia, and inability to stand and walk. The man developed a febrile meningeal syndrome and a hyperintense lesion of the splenium, which lasted for two months. Neurological changes, optic nerve edema, and urinary retention have resolved over the course of seven months. We think that the prolonged but transient lesion of the splenium may have been caused by encephalitis of viral origin.
Keywords: dospělí; Time Factors; encefalitida; časové faktory; corpus callosum; Humans; lidé; Encephalitis; mužské pohlaví; Male; Adult; Corpus Callosum